2017
DOI: 10.4103/0253-7176.203127
|View full text |Cite
|
Sign up to set email alerts
|

Personality Profile and Short-term Treatment Outcome in Patients with Alcohol Dependence: A Study from South India

Abstract: Background:Studying personality profiles allows researchers to generate important hypotheses in risk factors and correlates of alcohol use/misuse. Studies examining the association between personality traits and treatment outcome are limited in India. We studied the correlation between personality and treatment outcome in patients with alcohol dependence.Methods:Adult participants with alcohol dependence were recruited from the inpatient and outpatient wards of de-addiction unit of a tertiary care facility in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Individuals with lower levels of extraversion presented higher difficulty in social interaction. Thus, the use of these substances can be reinforced since it enables social interactions (Soundararajan et al, 2017). These personality characteristics are possibly considered risk factors for substance use, considering their connection with impulsive behaviors, lack of inhibitory control, and lack of planning.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals with lower levels of extraversion presented higher difficulty in social interaction. Thus, the use of these substances can be reinforced since it enables social interactions (Soundararajan et al, 2017). These personality characteristics are possibly considered risk factors for substance use, considering their connection with impulsive behaviors, lack of inhibitory control, and lack of planning.…”
Section: Resultsmentioning
confidence: 99%
“…However, few studies have investigated personality traits and psychopathological symptoms in substance users (Martínez-Loredo et al, 2021), particularly in outpatient treatment with a different clinical profile from patients admitted to psychiatric units. The literature presents studies focusing on the treatment of inpatients (Soundararajan et al, 2017), the majority including patients undergoing involuntary treatment (García-Marchena et al, 2018). Thus, this study aimed to characterize personality traits of adults with substance use disorders, in order to verify the association between personality traits, psychopathological symptoms, and impulsivity in substance users in outpatient treatment, and to investigate the predictive value of personality traits for the manifestation of psychopathological symptoms and impulsivity.…”
Section: Introductionmentioning
confidence: 99%
“…Several reports have highlighted the role of PDs in the treatment outcome of alcohol-dependent patients. [ 2 , 3 , 16 ] One recent meta-analysis[ 17 ] did not find any difference in treatment outcomes of alcohol-dependent patients with and without PDs. However, the authors have reported the quality of evidence of all the included studies to be low or very low.…”
Section: Discussionmentioning
confidence: 99%
“…Research on poor treatment utilization/retention and mechanisms to enhance access and compliance might help improve this treatment gap (Tripathi et al, 2020). Studies across Indian and global contexts show personality impairments as highly comorbid with SUDs (Köck & Walter, 2018; Soundararajan et al, 2017). They play a role in the initiation and maintenance of SUDs, and can predict poor treatment response, early dropouts, frequent lapses and shorter abstinence periods (Kienast et al, 2014;Minkoff, 2016).…”
Section: Introductionmentioning
confidence: 99%